Phosphate Solubilizing Bacteria (PSB) Isolation from Tomato Rhizospheres at Koka District, Ethiopia - Dereje Haile; Bizuayehu Tesfaye; Fassil Assefa (Turkish Journal of Agriculture: Food Science and Technology)
Phosphorous is an essential macronutrient for plant growth and development. Most of the soil is deficient in plant available phosphorous and due to economic limitations majority of Ethiopian farmers applied inadequate fertilizers. It is essential to stabilize a mechanism to access P for plants with an efficient, cheap, and eco-friendly approach for enhanced crop growth and production. The main objective of this study was to screen efficient phosphate solubilizing bacteria from tomato rhizosphere soil. Using halo zone formation on PVK agar medium, more than 400 PSB isolates were isolated from 13 rhizosphere soil samples. By evaluating SI, texture in the culture-re-culturing process, liquid medium pH change efficiency and growth rate, upmost three promising PSB isolates (K-1-29, K-10-27, and K-10-41) were selected. Incubation of the isolates in PVK broth for five days showed significant pH reduction. For instance, isolate K-10-41 showed significant pH change (4.02) which indicates the organic acid production. Isolation and evaluation of efficient phosphate solubilizing bacteria maintain soil fertility, promote plant growth, induce plant response to pathogens, reduce agrochemical consumption and promote sustainable agriculture. Therefore, these selected PSB isolates need further detailed study for taxonomic identification, plant growth promotion, host range, and phytopathogen response. Local isolation improves environmental adaptation and indigenous competition.